Heidegger, techne as a mode of truth and the end of philosophy - Provinciatto, Luís Gabriel (Sofia, 2024)
This paper analyzes the relationship between τέχνη and ἀλήθεια, showing how Heidegger draws on these Greek conceptions to assert that modern technology represents the end of philosophy. The approach is to read Heidegger through his own work, taking as a starting point his 1924/1925 lectures on Plato’s Sophist. In these lectures, while preparing the interpretation of Plato’s dialogue, Heidegger demonstrates that in Aristotle, ἐπιστήμη and τέχνη are the two immediate modes of ἀληθεύειν and pertain, respectively, to that which provides knowledge (ἐπιστημονικόν) and reflection (λογιστικόν). In his later work, Heidegger postulates that modern technology, whose essence is termed Ge-stell, marks the end of philosophy. In this context, the article aims to develop a framework for understanding modern technology as the culmination of philosophy, based on Heidegger’s interpretation of τέχνη in Plato and Aristotle. It argues that modern technology is not merely a means to an end, but a mode of truth that has even subordinated philosophical thought, resulting in the dominance of technology over all spheres of existence.
Keywords: technology; truth; the end of philosophy; Aristotle; Plato